(untitled) (European Bison Conservation Newsletter, 2011)
Among the numerous problems in protection and breeding European bison in the Bieszczady the most significant one is the issue of tuberculosis threat. The first case of tuberculosis in European bisons in the Bieszczady was reported in March 1996 in former Forest Division Brzegi Dolne. After recognition of the threat, including diagnostic culls in 1997–2000, it was decided to eliminate the herd of bison from this area, due to widespread Mycobacterium tuberculosis infection. Elimination took place in 2001: from the herd of 12 individuals, it was managed to cull 6 animals, finding tuberculosis in all of them. The others left the area of Forest Division Brzegi Dolne and probably joined other herds, possible being a source of infection. The issue of tuberculosis of European bison came back on 27th February 2010 when in Forest Division Stuposiany the dead cow of European bison was found with confirmed presence of acid-fast bacillus of Mycobacterium bovis. One year later, on 19th February 2011, in the same forest division the dead European bison (cow) had been found and a few days later on 3rd March 2011 in the nearby vicinity dying European bison (bull) was shot – tuberculosis was confirmed in both cases. Several weeks later on 27th March 2011 in Forest Division Stuposiany (near the border with Bieszczady National Park) the herd of European bison was spotted, in which three individuals indicating obvious index event – emaciated, dejected, stood aside of herd and they allowed to approach very close distance to them. Unfortunately, those bison went to Bieszczady National Park area and were impossible to be found. These cases clearly indicate that in the area of existence of herds from Forest Division Stuposiany and Bieszczady National Park we have new active outbreak of tuberculosis. Hitherto results are not representative enough for full evaluation of the health situation of European bison in the Bieszczady, therefore it is necessary to conduct further monitoring for tuberculosis. There also has to be done ad hoc attempt to isolate the herd existing in other forest divisions. The final decision concerning the modus operandi for herds living in Forest Division Stuposiany and in Bieszczady National Park should be made after recognition of epizootic situation, based on clinical reviews of tuberculosis in all herds of European bison population in the Bieszczady, supplemented with environmental examination as well as on the basis of the epidemiological analysis of obtained research results.